Discussion of Precision Heat Treatment and Anti-Fatigue Manufacturing of Gear - Jinsheng Lu; Baokui Li (Jixie chuandong)
The development course of gear manufacturing technology is reviewed， the characteristics of three generation manufacturing technology are compared， the advancement of ‘no stress concentration’ anti-fatigue manufacturing is interpreted. The development situation， advanced technology and its mechanical property of three kinds of gear surface hardening precision heat treatment as key basic technology are discussed including carburization， nitriding and induction quenching. By optimizing and controlling the hardness gradient， residual stress field， micro structure and distortion of surface metamorphic layer， the innovation and development of gear precision heat treatment， the gear anti-fatigue performance is greatly improved， and then solve the three major problems of gears such as heavyweight， short life and low reliability. The development trend of gear anti-fatigue precision heat treatment is predicted to be ‘super hardening’， deep case hardening’， ‘combined hardening’， and ‘vacuum ion heat treatment’.